Pendampingan Masyarakat Desa dalam Mewujudkan SDGs (Sustainable Development Goals) di Desa Plumbon dan Tantangan yang Dihadapi - Ahmad Zuber; Adem Esen; Drajat Tri Kartono; Aris Arif Mundayat; Rezza Dian Akbar; Theofilus Apolinaris Suryadinata (Society, 2024)
Rural community development is intrinsically linked to achieving the Sustainable Development Goals (SDGs) for villages. This study aims to analyze the implementation of the Village SDGs in Plumbon Village (PV). Employing a qualitative research approach, data were collected through Focus Group Discussions (FGDs) and in-depth interviews. The findings reveal that the implementation of the Village SDGs in PV has achieved notable success across several key components, including the establishment of a safe and comfortable village, a peaceful and just community, the eradication of hunger, strong women's participation, sustainable consumption, and production practices, reduced inequalities, enhanced health and well-being, access to quality education, environmental conservation efforts, and the development of dynamic institutional structures. However, the study also identifies several challenges, such as improving infrastructure, empowering the community, managing agricultural and environmental resources, enhancing education and healthcare services, optimizing public service delivery, fostering effective communication and community engagement, and addressing shared aspirations and expectations within the community.